The antiproliferative effect of mesenchymal stem cells is a fundamental property shared by all stromal cells. - Jones, S; Horwood, N; Cope, A; Dazzi, F (2007)
Although it has been widely demonstrated that human mesenchymal stem cells exert potent immunosuppressive effects, there is little information as to whether more mature mesenchymal stromal cells (SC) share the same property. Accordingly, we set out to test the ability of SC from different human tissues to inhibit the proliferation of PBMC following polyclonal stimuli. Chondrocytes, as well as fibroblasts from synovial joints, lung, and skin, were used as a source of SC. Irrespective of their differentiation potential and/or content of progenitor cells, SC from all tissues exhibited antiproliferative functions. This was in marked contrast to parenchymal cells. Although SC did not interfere with early T lymphocyte activation, they arrested stimulated T cells in the G(0)/G(1) phase of the cell cycle and rescued them from apoptosis. In addition, IFN-gamma and TNF-alpha production were reduced. We observed that the inhibitory effect is ultimately mediated by soluble factors, the production of which requires SC to be licensed in an inflammatory environment by cell contact. We conclude that the immunosuppressive effect of mesenchymal cells is not confined to multipotent stem cells, but is a fundamental characteristic of all stroma. Our data suggest that SC, appropriately licensed, regulate T cell homeostasis.